Denmark : Selected Issues-The Danish Fiscal Framework-Looking Back and Ahead. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper examines Denmark's fiscal framework. It evaluates its sufficiency with respect to accommodating medium-to-long-term demographic spending increases and future challenges facing the tax system. It reviews the framework's transparency, consistency and enforceability, taking into account local government responsibilities. The paper concludes that Denmark has already made commendable progress with public finance consolidation, changing relatively large budget deficits to solid surpluses and almost halving the debt-to-GDP ratio since 1993. The fiscal framework is transparent and appears to enjoy wide public acceptance.